RANCANG BANGUN BACK-END SISTEM INFORMASI CAPAIAN PEMBELAJARAN LULUSAN (CPL) MENGGUNAKAN LARAVEL - Faniel Sianipar; Wahyu Eko S; Yessi Mulyani; Gigih Forda Nama (Universitas Lampung, 2026)
Higher education plays a strategic role in producing qualified graduates through outcome based curricula. However, at the University of Lampung, the calculation of Graduate Learning Outcomes (Capaian Pembelajaran Lulusan/CPL) has not been carried out systematically, making curriculum evaluation less optimal. This study aims to develop the back end of a CPL Information System using the Laravel framework and the Agile Kanban approach. The research stages include literature review, analysis of functional and non functional requirements, system design with a modular architecture, and implementation of APIs to support management of CPL, CPMK, classes, students, and accounts. Testing was performed using PHPUnit with dummy data to ensure core functionalities meet requirements. The results show a modular and well organized back end API ready for front-end integration, although further testing with real data and code refactoring are needed to improve quality. This system is expected to support study programs in curriculum evaluation and accreditation processes more effectively.